2022
DOI: 10.1177/10732748221144458
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Paraneoplastic Syndromes: A Critical Review of Diffuse Uveal Melanocytic Proliferation and Autoimmune Retinopathy

Abstract: Background: Dozens of paraneoplastic syndromes affect the visual system ranging from conjunctival pemphigoid to encephalopathy of the occipital cortex. The most profiled ocular syndromes are bilateral diffuse uveal melanocytic proliferation (BDUMP) and the autoimmune retinopathies. Purpose: To review the critical features of these 2 entities then concentrate on advancements in treatment made within the last 10 years. Study Design: Literature review with structured data abstraction. Results: Major insights i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 109 publications
(194 reference statements)
0
9
0
Order By: Relevance
“…Carbonic anhydrase II is an essential metallo-enzyme for the regulation of acid-base balance and energy homeostasis in human cells. Antibodies against carbonic anhydrase II have been reported in both autoimmune-and cancer-associated retinopathy including hematological cancer (7). In our patient a direct activity of the monoclonal IgM against retina antigens was not tested.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Carbonic anhydrase II is an essential metallo-enzyme for the regulation of acid-base balance and energy homeostasis in human cells. Antibodies against carbonic anhydrase II have been reported in both autoimmune-and cancer-associated retinopathy including hematological cancer (7). In our patient a direct activity of the monoclonal IgM against retina antigens was not tested.…”
Section: Discussionmentioning
confidence: 82%
“…The presence of anti-retinal antibodies should be interpreted in the context of other findings, due to lack of specificity and a universally accepted detection technique across laboratories. Indeed, it has been reported that anti-retinal antibodies may be found in up to one third of healthy individuals (7). In cases of cancer-associated retinopathy, antibodies against tumor-related antigens present cross-reactivity with retinal antigens, and these auto-antibodies target retinal cells and induce apoptosis (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gass's "leopard spots", characterizing the reticulated ocular fundus pattern, are colloquially known as the "gyrate pattern". While the reticulated depigmentation pattern is characteristic of BDUMP, its diagnostic specificity is tempered by its occurrence in other bilateral conditions such as metastatic cancer, leukemic choroidal infiltration, and lymphoma, all of which can manifest bilaterally [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is theorized that either a substance secreted by the tumor or an antibody stimulated by the tumor triggers the benign proliferation of choroidal melanocytes [5]. Extensive discussions on the pathologic correlates of BDUMP have been documented in nearly 100 cases [3], underscoring the ongoing efforts to unravel its intricacies.…”
Section: Introductionmentioning
confidence: 99%